As convenções e os acordos coletivos de trabalho como fontes do Direito Previdenciário - Ferraro, Suzani Andrade (2015)
The thesis has the objective to examine the agreements and collective bargaining agreements as a pension right sources to discuss how social security rights are incorporated into the employee's equity during and after the term of the agreement and collective bargaining agreements. In this regard it is important to reconsider the concepts of "sources of law" from the constitutional right to the sources are examined from the social security law. There are four specific objectives of this thesis: (i) conceptually define the sources of law; (ii) investigate the agreements and collective bargaining agreements; (iii) analyze the legal system of social security; (iv) research the pension rights from the conventions and collective bargaining agreements. The research problem of this doctoral thesis is the following: (1) the agreements and collective bargaining agreements are sources of social security law? This central problem converges another problem: (2) the pension rights from the conventions and collective agreements persist after the expiry of validity of the agreements and collective bargaining agreements? As hypotheses, the following were formulated: (1) the conventions and collective agreements are sources of social security law. (2) The pension rights from the conventions and collective agreements persist after the expiry of validity of the agreements and collective bargaining agreements based on the principle of sealing the setback. The research of the thesis is relevant scientific and socially for three reasons: (1) provides a legal analysis between two fields of law (labor law and social security law); (2) extends the research object of this thesis to give rise to a transdisciplinary research to the agreements and collective bargaining agreements, which are collective bargaining agreements, can be sources of social security law; (3) the pension rights from the conventions and collective labor agreements are fundamental social rights highlighted social relevance in that the professional categories that celebrate the conventions and collective agreements can fight for the rights gained are permanently incorporated into the heritage collective and individual workers